7/8h+2=3/8h-2

Simple and best practice solution for 7/8h+2=3/8h-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7/8h+2=3/8h-2 equation:



7/8h+2=3/8h-2
We move all terms to the left:
7/8h+2-(3/8h-2)=0
Domain of the equation: 8h!=0
h!=0/8
h!=0
h∈R
Domain of the equation: 8h-2)!=0
h∈R
We get rid of parentheses
7/8h-3/8h+2+2=0
We multiply all the terms by the denominator
2*8h+2*8h+7-3=0
We add all the numbers together, and all the variables
2*8h+2*8h+4=0
Wy multiply elements
16h+16h+4=0
We add all the numbers together, and all the variables
32h+4=0
We move all terms containing h to the left, all other terms to the right
32h=-4
h=-4/32
h=-1/8

See similar equations:

| 6s+3s-5s-s+2s=20 | | 14+19+q/3=17 | | 3(f-5)=5(2f+11 | | 188=m=80 | | 1900x+150=1500+275 | | 13k+k-13k=7 | | 4(-4x-21)=30(-9-2x) | | 2)a-1)-5a=7 | | -56=j+-22 | | 8x+4=9x=8 | | 32=f−54 | | 5^(-x+7)=12^7x | | 33+8b=5+4(2b+7) | | 10m^2=2+3m | | 1r/20=-2 | | -12.93+5.2n=7.3n-6 | | P+p+2+p+4=-9 | | q-8=4 | | 10n-0.375=0.1n-0.37 | | 8^(2x)+8^(x+1)+15=0 | | n+7/3=9/2 | | -5.96a+2.7a=-1.7a+1.01a+12.4902 | | n+7/6=9/2 | | 8g=-96 | | n+7/6=8/2 | | b+22=74 | | 2e-7=+11 | | n+21/3=41/2 | | p+18=43 | | 3(-4-4n)=-6(2n+1) | | 2a^2+2a+4=0 | | -3/4z-6=3/4 |

Equations solver categories